Intelligent data engineering and automated learning – IDEAL 2019 : 20th International Conference, Manchester, UK, November 14-16, 2019, Proceedings.: 20th International Conference, Manchester, UK, November 14-16, 2019, Proceedings. Part I (2019) - Unknown
No abstract available